1988
DOI: 10.1093/rheumatology/27.2.94
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Index for Erosive Changes in the Hands, Feet, and Cervical Spines in Early Rheumatoid Arthritis

Abstract: Clinical and laboratory measurements taken at the onset of rheumatoid arthritis in 149 patients were compared with the severity of radiological changes seen at 3 years in the hands and feet, and cervical spine. The strongest association with the severity of peripheral radiological damage was rheumatoid factor (p less than 0.0001 for both the latex titre and RAHA titre). Subluxation of the cervical spine was associated only with the presence of HLA-Dw2 (p less than 0.02) and HLA-B7 cross-reacting group (p less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…Men are more commonly affected than women, although this may represent the sex-related expression of HLA-B27 spondyloarthropathy. Clinically, patients often exhibit features of both classical RA and spondyloarthropathy, and are occasionally defined as having the" overlap syndrome" [12]. Patients more frequently have symptoms of cervical spine or sacroiliac joint pain than do patients with RA alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Men are more commonly affected than women, although this may represent the sex-related expression of HLA-B27 spondyloarthropathy. Clinically, patients often exhibit features of both classical RA and spondyloarthropathy, and are occasionally defined as having the" overlap syndrome" [12]. Patients more frequently have symptoms of cervical spine or sacroiliac joint pain than do patients with RA alone.…”
Section: Discussionmentioning
confidence: 99%
“…Fallahi et al [6] in a review of 292 patients with RA found that the presence of the HLA-B27 antigen did not alter the radiographic picture regarding joint distribution, pattern and mode of onset, disease progression, and the rate of occurrence of postoperative heterotopic ossification. However, several other reports suggest an increased incidence of sacroiliac joint involvement in HLA-B27-positive RA patients [3,4,12]. Most recently, Jurik et al [9] examined a group of 11 HLA-B27-positive, seropositive RA patients and age-matched B27-negative control patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rheumatoid disorders of the cervical spine are known to be associated with the extent of erosions in the peripheral joints and the HLA status, as well as with the presence of rheumatoid factor (RF) and rheumatoid nodules (6)(7)(8)(9)(10). Continuous disease activity predicts the development of erosions in peripheral joints (11,12).…”
mentioning
confidence: 99%
“…However, of these and other features analyzed in a study using discriminant function analysis, only a combination of RF (by sheep cell agglutination and by latex fixation), hemoglobin level, and platelet count successfully predicted radiologic outcome in 72%. This was confirmed in 79% in a separate group (19). Improvement in these values is essential to the clinician intending to use powerful second-line agents in early disease.…”
Section: High Levels Of Agalactosyl Igg (Gal[o])mentioning
confidence: 78%